Modelo fatorial para dados categóricos ordinais com fatores explicados por variáveis auxiliares - Viana, Alana Tavares (2021)
Depression is a mood disorder commonly measured through a 12-question questionnaire. From this, a score that measures depression is calculated. In this paper, we present two proposals to summarize the questions in this questionnaire in one or two factors considering the uncertainty present in the data, in addition to incorporating auxiliary variables that explain this factor(s). For this, we proposed a factorial model for ordinal categorical data with factors explained by auxiliary variables, and validate the methodology and the inference method used.